Making Sense of Law Reform-A Case Study of Workers' Compensation Law Reform in Ontario 1980 to 2012 - King, Andrew G. (Université d'Ottawa / University of Ottawa, 2014)
This thesis is a case study from 1980 to 2012 of law reform applied to workers’ compensation in Ontario. It aims to understand the promise of law reform and its implementation from the standpoint of injured workers. The study is structured in three parts. Part One constructs an analytical framework drawing on legal theories and principles of adjudication. It provides a brief history of the Ontario Workers’ Compensation Board, its powers and adjudicative practices prior to the reforms. Part Two summarizes reform in Ontario’s workers’ compensation law from 1980 to 2012. The description is organized into five periods reflecting significant shifts in direction. It focuses on government recommendations for reform, identifies and describes key legislative changes, and explores changes to governance, appeals and adjudication. Legislation, case law, policy and practice are reviewed. Part Three reviews the evidence of the impact of the Ontario reforms on a particular group: unemployed, permanently disabled workers. While the Board refuses to track the economic status of injured workers, research suggests poverty and stigma face many. Conclusions suggest that Ontario’s workers’ compensation system was transformed from one established to address the interests of workers and employers separately to one that balances those interests and now into one that privileges the interests of employers. Workers’ interests are a cost to be reduced. The prospect of law reform as an empirically driven process to address injustice has been corrupted by a focus on correctness with fairness as an afterthought. Cette thèse étudie les réformes de la législation ontarienne en matière d'indemnisation pour les accidents du travail apportées entre 1980 et 2012. Elle vise à comprendre, du point de vue des travailleurs accidentés, les promesses des réformes et leur mise en oeuvre. L'étude est structurée en trois parties. La première partie fournit un cadre théorique ancré sur certaines théories juridiques et sur les principes régissant la prise de décision. Elle fournit une courte historique de la Commission des accidents du travail de l'Ontario, en regard de ses pouvoirs et pratiques décisionnelles avant les réformes. La deuxième partie fait la synthèse de la réforme de la législation ontarienne en matière d'accidents du travail de 1980 à 2012. Elle se divise en cinq périodes reflétant les réorientations importantes. Elle aborde les recommandations gouvernementales, décrit les modifications législatives et explore les changements apportés au niveau de la gouvernance, des appels et des modalités de prise de décision. La législation, la jurisprudence, les directives et les pratiques sont étudiées. La troisième partie analyse, à la lumière des statistiques et les recherches scientifiques sur le sujet, l'impact des réformes ontariennes sur un groupe particulier: les travailleurs porteurs d'atteintes permanentes et qui sont sans emploi. Alors que la Commission refuse de documenter le statut économique des travailleurs accidentés, la recherche suggère que plusieurs font face à la pauvreté et la stigmatisation. Les conclusions de la thèse suggèrent que le système d'indemnisation des accidentés du travail de l'Ontario est passé d'un système conçu pour répondre aux intérêts des travailleurs et des employeurs de manière séparée à un système qui a cherché l'équilibre entre ces intérêts, pour, maintenant, privilégier les intérêts des employeurs. Les intérêts des travailleurs sont des coûts à être réduits. La perspective de la réforme du droit en tant que processus fondé sur les données scientifiques pour répondre à l'injustice a été corrompue par un focus sur le caractère correct des décisions, et l'équité est devenue une considération qui vient en dernier lieu.
Keywords: law and social justice; law reform; workers' compensation; administrative law; economic analysis of law; therapeutic jurisprudence; access to justice